2022
DOI: 10.1108/imds-11-2021-0662
|View full text |Cite
|
Sign up to set email alerts
|

The effects of appearance personification of service robots on customer decision-making in the product recommendation context

Abstract: PurposeThe COVID-19 pandemic has made contactless services such as those provided by robots increasingly pervasive. Some stores are gradually adopting service robots to sell products, which has not been explored in previous research. This study aims to explore how appearance personification of service robots affects customer decision-making in the product recommendation context.Design/methodology/approachBased on authentic in-store product recommendation service interactions, an experiment for three simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 75 publications
(132 reference statements)
2
6
0
Order By: Relevance
“…The results show that personified communication significantly impacts consumers’ attitudes through perceived usefulness between enterprises and consumers. Such results are consistent with previous studies based on TAM [ 5 , 17 , 18 , 19 , 20 ]. Also, we find that personified communication positively impacts users’ purchase attitudes through perceived interaction, which is a new finding of this study.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results show that personified communication significantly impacts consumers’ attitudes through perceived usefulness between enterprises and consumers. Such results are consistent with previous studies based on TAM [ 5 , 17 , 18 , 19 , 20 ]. Also, we find that personified communication positively impacts users’ purchase attitudes through perceived interaction, which is a new finding of this study.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
“…In addition, the influence of attitude on purchase intention is also substantial, consistent with previous studies reporting that attitude positively affects behavioral intention [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 24 ]. In addition, consumers’ cognitive need for knowledge can adjust the path of perceived usefulness, indirectly influencing consumers’ purchase intention.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies and real life examples have shown the advantage of anthropomorphism, when we use closeness implying language in communication, it may excite consumers' positive attitudes toward the brand 7 , that may lead a favorable effect on brand evaluation. Song 8 found the effect of anthropomorphism on trustworthiness, the latest research ndings reveals effects of anthropomorphism on customers' satisfaction 9 , customers' decisions in the context of product recommendations 10 , and the in uence on COO effects 11 . We expect to further the research on the COO stereotypes and explore factors in uencing the effectiveness of anthropomorphism on COO stereotypes, to deepen the research eld of anthropomorphism and stereotype.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have found that brand image also has an impact on the country's image 9 , and the interaction of the brand image and the country's image may lead to the formation of deeper stereotypes, so how to reduce COO stereotypes becomes more and more important for developing countries in international competition. Previous studies and real-world examples have shown the advantages of anthropomorphism, when a brand adopts human-like language in communication, it may excite individuals' positive attitudes toward the producrt 10 , the latest research findings reveal the effects of anthropomorphism on customers' satisfaction 11 and product recommendations 12 . Psychological factors such as individuals' mindset could also influence their preference for products.…”
mentioning
confidence: 95%